Hypotension-Avoidance Versus Hypertension-Avoidance Strategies in Noncardiac Surgery - Maura Marcucci; Thomas Painter; David Conen; В. В. Ломиворотов; Daniel I. Sessler; Matthew T.V. Chan; Flávia K. Borges; Kate Leslie; Emmanuelle Duceppe; María José Martínez‐Zapata; Chew Yin Wang; Denis Xavier; et al. (2023)
Background: Among patients having noncardiac surgery, perioperative hemodynamic abnormalities are associated with vascular complications. Uncertainty remains about what intraoperative blood pressure to target and how to manage long-term antihypertensive medications perioperatively. Objective: To compare the effects of a hypotension-avoidance and a hypertension-avoidance strategy on major vascular complications after noncardiac surgery. Design: Partial factorial randomized trial of 2 perioperative blood pressure management strategies (reported here) and tranexamic acid versus placebo. (ClinicalTrials.gov: NCT03505723) Setting: 110 hospitals in 22 countries. Patients: 7490 patients having noncardiac surgery who were at risk for vascular complications and were receiving 1 or more long-term antihypertensive medications. Intervention: In the hypotension-avoidance strategy group, the intraoperative mean arterial pressure target was 80 mm Hg or greater; before and for 2 days after surgery, renin–angiotensin–aldosterone system inhibitors were withheld and the other long-term antihypertensive medications were administered only for systolic blood pressures 130 mm Hg or greater, following an algorithm. In the hypertension-avoidance strategy group, the intraoperative mean arterial pressure target was 60 mm Hg or greater; all antihypertensive medications were continued before and after surgery. Measurements: The primary outcome was a composite of vascular death and nonfatal myocardial injury after noncardiac surgery, stroke, and cardiac arrest at 30 days. Outcome adjudicators were masked to treatment assignment. Results: The primary outcome occurred in 520 of 3742 patients (13.9%) in the hypotension-avoidance group and in 524 of 3748 patients (14.0%) in the hypertension-avoidance group (hazard ratio, 0.99 [95% CI, 0.88 to 1.12]; P = 0.92). Results were consistent for patients who used 1 or more than 1 antihypertensive medication in the long term. Limitation: Adherence to the assigned strategies was suboptimal; however, results were consistent across different adherence levels. Conclusion: In patients having noncardiac surgery, our hypotension-avoidance and hypertension-avoidance strategies resulted in a similar incidence of major vascular complications.